Діяльність Європейського Союзу щодо протидії торгівлі людьми - Войціховський, А. В.; Voytsihovskyi, A. V.; Андрій Войціховський (Право і Безпека. - 2016. - № 2 (61). - С. 18–24, 2016)
Досліджено особливості діяльності ЄС у боротьбі з торгівлею людьми; здійснено аналіз міжнародних документів ЄС у зазначеній сфері. Визначено нові організаційно-правові механізми ЄС щодо протидії торгівлі людьми.

Ukraine today is one of the countries of origin and transit of victims of human trafficking to the EU Member States, thus, research and harmonization of national legislation with EU legal norms in this area is of great theoretical and practical importance for Ukraine and other countries. The objective of this article is to study the characteristics of the European Union activities in the fight against human trafficking; analysis of international documents of the EU in this area (resolutions, declarations, framework decisions, directives, strategies); determining new organizational and legal mechanisms of the EU in the sphere of combating human trafficking. Special attention within the article is paid to the research of the activities of Europol and Eurojust – the EU institutions, which play an important role in establishing international cooperation in the fight against human trafficking. As a result, the author has noted that the problem of human trafficking within the EU is paid much attention. At the EU level serious efforts exerted to combat the sources of this problem. Any manifestations of human trafficking are considered by all EU institutions as one of the most serious human rights violations, and the states should make joint efforts to combat this phenomenon. A characteristic feature of the EU policy on combating human trafficking is that the main attention of this integration association focuses primarily on ensuring human rights – the victims of this phenomenon, on creating the conditions for their reintegration and socialization, and this, in turn, will improve the situation to bring to justice those responsible. This approach should serve as a model for legislative activities in combating human trafficking in Ukraine.

Исследованы особенности деятельности ЕС в борьбе с торговлей людьми; осуществлён анализ международных документов ЕС в указанной сфере. Определены новые организационно-правовые механизмы ЕС по противодействию торговле людьми.
Activities of the European Union on combating human trafficking
Деятельность Европейского Союза по противодействию торговле людьми
Keywords: Міжнародне право .International Law. Международное право; Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Європейський Союз; торгівля людьми; Група експертів ЄС щодо торгівлі людьми; Європейський координатор з протидії торгівлі людьми; Європол; Євроюст; протидія торгівлі людьми; European Union; human trafficking; EU Expert Group on Human Trafficking; European coordinator on combating human trafficking; Europol; Eurojust; Европейский Союз; торговля людьми; Группа экспертов ЕС по торговле людьми; Европейский координатор по противодействию торговле людьми; Европол; Евроюст